Persepsi Masyarakat terhadap Pelayanan Pembayaran Pajak Kendaraan Bermotor secara Online - Widodo, Wahyu; Mirnawati, Mirnawati (Tapis: Jurnal Penelitian Ilmiah, 2024)
This study aims to determine the community's perception of online motor vehicle tax payment services, regarding simplicity, clarity, certainty of completion time, employee responsibility, completeness of facilities and infrastructure, employee behavior, and comfort. This research uses qualitative descriptive methods, while data collection is carried out by observation, interview, and documentation techniques. The data analysis technique used is an interactive analysis including data collection, data reduction, data presentation, and then concluding. The validity of the data used is the source triangulation technique and the method triangulation. The results of this study show that the perception of the Metro City community towards online motor vehicle tax payment services is quite good. However, there is still a need for additional information boards. A longer queue and completion time in paying their motor vehicle tax makes them use third-party services.